Calibration of omnidirectional wheeled mobile robots: method and experiments. Issue 6 (September 2013) - Maddahi, Yaser; Maddahi, Ali; Sepehri, Nariman
SUMMARY Odometry errors, which occur during wheeled mobile robot movement, are inevitable as they originate from hard-to-avoid imperfections such as unequal wheels diameters, joints misalignment, backlash, slippage in encoder pulses, and much more. This paper extends the method, developed previously by the authors for calibration of differential mobile robots, to reduce positioning errors for the class of mobile robots having omnidirectional wheels. The method is built upon the easy to construct kinematic formulation of omnidirectional wheels, and is capable of compensating both systematic and non-systematic errors. The effectiveness of the method is experimentally investigated on a prototype three-wheeled omnidirectional mobile robot. The validations include tracking unseen trajectories, self-rotation, as well as travelling over surface irregularities. Results show that the method is very effective in improving position errors by at least 68%. Since the method is simple to implement and has no assumption on the sources of errors, it should be considered seriously as a tool for calibrating omnidirectional mobile having any number of wheels.